Thermal patterns at a curved liquid surface - Lim, Hong Da (2017)
The dynamics of evaporating droplets are essential to several small scale biomedical and technological and industrial scale applications involving mass and heat transfer. To comprehend the relationship between physical underlying parameters and surface thermal patterns, many researches and studies have been carried out. Of which, majority of these previous studies were carried out on droplets under the conditions of drying out. Hence, infrared thermography (IR) method which utilizes emission of infrared, allowing spectrums not visible to the naked eye to be visualized, is being employed to achieve that goal. This study discusses the experimental results of deionized water and aims to facilitate the understanding of the underlying factors affecting the thermal patterns which are created and determining the volumetric flow-rate required to maintain a stable droplet. Several types of fluids were tested via a non-destructive, noncontact test method called infrared visualization method. In the set-up of the experiment, a droplet of liquid was created on a copper stage and monitored using equipment such as camera and infrared cameras. To observe the droplet’s thermal patterns, the infrared camera is mounted directly above the droplet to capture the top image while the geometric parameters’ evolution is followed using the laterally placed camera. These parameters include the pressure and temperature of the chamber. Two K-type thermocouples are connected to the copper stage to obtain the temperature reading of the stage. The conditions for this experiment are recorded by means of type K thermocouple and pressure reading. The temperatures being investigated are ranged between room temperature to 75C. De-ionized water is injected through a thin pipe into the copper stage and the droplet is left to stabilize in the chamber comprising of 700 ± 10 mbar pressure to 900 ± 10 mbar pressure. As the above experiments are mostly targeted at pure liquids, future works can be conducted on mixtures of varying concentrations which may alter the thermal conductivity, hence affecting the thermal patterns.